Corporate social responsibility and expected benefits in the financial sector: empirical evidence from Serbia - Nikolić, Jelena; Tošić, Bojana; Zlatanović, Dejana (Anali Ekonomskog fakulteta u Subotici, 2023)
As the pillar of the economy, financial institutions play important role in implementation of the concept of corporate social responsibility (CSR). The paper is focused on CSR in the financial sector, i.e. the perception of employees in banks and insurance companies in Serbia on the level of development of CSR regarding its external dimensions, such as responsibility toward beneficiaries, community and environment. The aim is to identify the employees’ perceptions of external aspects of CSR in the financial sector, as well as to determine the impact of selected external aspects on the expected CSR benefits. The results of the conducted empirical research demonstrate a positive attitude of employees in financial institutions in the Republic of Serbia towards external aspects of CSR, as well as statistically significant impact of CSR towards beneficiary and environment on the expected CSR benefits. Additionally, the results indicate that CSR towards the community does not affect the expected benefits. Accordingly, we identified some practical and theoretical implications that can serve as a basis for creating and implementing a strategic approach to CSR in financial institutions